2017
DOI: 10.1002/bab.1553
|View full text |Cite
|
Sign up to set email alerts
|

Effectively enhancing cytotoxic and apoptotic effects of alpha‐momorcharin by integrating a heparin‐binding peptide

Abstract: Alpha-momorcharin (α-MMC), a type I ribosome-inactivating protein, has attracted a great deal of attention because of its antitumor activity. However, the cytotoxicity of α-MMC is limited due to insufficient cellular internalization in cancer cells. To enhance the cytotoxicity of α-MMC, a heparin-binding domain derived from heparin-binding epidermal growth factor (named heparin-binding peptide [HBP]) was used as a cell-penetrating peptide and fused to the C-terminus of α-MMC. This novel α-MMC-HBP fusion protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Moreover, this region is also part of the heparin‐binding domain of BMP4. Previous studies by our group found that the heparin‐binding domains of many proteins are rich in basic amino acid residues, which can bind to extracellular heparin polysaccharides and quickly attach to the cell surface, which can be used as candidates for the development of highly efficient cell‐penetrating peptides (Li et al, 2020; Lu et al, 2016; Tan et al, 2017). Therefore, T3BP not only has the ability of target binding, but also has a good autonomous membrane penetration ability due to its rich basic amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this region is also part of the heparin‐binding domain of BMP4. Previous studies by our group found that the heparin‐binding domains of many proteins are rich in basic amino acid residues, which can bind to extracellular heparin polysaccharides and quickly attach to the cell surface, which can be used as candidates for the development of highly efficient cell‐penetrating peptides (Li et al, 2020; Lu et al, 2016; Tan et al, 2017). Therefore, T3BP not only has the ability of target binding, but also has a good autonomous membrane penetration ability due to its rich basic amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…α-Momorcharin (α-MMC) is a ribosomal inactivation protein extracted from bitter melon seeds. It hydrolyzes the N-C glycoside bond between adenine base and ribosome at position A4324 of ribosomal 28SrRNA in eukaryotic cells, and prevents the binding of elongator EF-2 to ribosome, thereby inhibiting protein synthesis [3]. Studies have shown that α-MMC exerts immuneregulatory effects on breast carcinoma, colorectal carcinoma, hepatoma, non-small cell lung cancer, epithelial cell cancer and glioma [4][5][6].…”
Section: Introductionmentioning
confidence: 99%